An Effect Health Promotion on Acceptance of Covid-19 Vaccine in Communities in the Work Area Sidangkal Puskesmas, Padang Sidempuan Selatan - Nerissa Nasriza; Santy Deasy Siregar; Chrismis Novalinda Ginting (Budapest International Research and Critics University, 2022)
Health Promotion is an effort to improve the community's ability to control health factors through learning from by, for, and with the community, so that they can help themselves, and develop community-based activities, according to local socio-cultural and supported by insightful public policies. The purpose of the study was to determine the effect of health promotion on the acceptance of the covid-19 vaccine in the community in the working area of the Sessionkal Public Health Center in 2021. The research used is research that uses a descriptive method with a qualitative approach. The research was conducted in the working area of the Sessionkal Public Health Center in 2021 with 7 core informants. The results of interviews with informants are still many who have not done the covid-19 vaccine. Informants' lack of knowledge about the covid-19 vaccine, lack of promotional media, a lot of slanted news about the covid-19 vaccine, and the lack of health worker outreach activities to the people of South Padangsidempuan. The results showed that there was no effect of health promotion using various promotional media on the acceptance of the covid-19 vaccine in the community in the working area of the Sessionkal Health Center.